2022
DOI: 10.3389/fmed.2022.847143
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Next-Generation Sequencing to Investigate Infectious Endophthalmitis of Brucella: A Case Report

Abstract: IntroductionBrucellosis is a systemic disease that exists prevalently in clinical manifestations. The symptoms present in organs such as the eyes (in ocular brucellosis) can lead to misdiagnosis or even failure to diagnose. Metagenomic Next-Generation Sequencing (mNGS), a high-throughput sequencing approach, could be applied for the detection of microorganisms.Case PresentationA 57-year-old female with acute right-eye vision loss, treated with clindamycin and dexamethasone sodium phosphate for 1.5 months, was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Afterwards, with the advent of an unbiased sequencing technique, the NGS of 16S rDNA amplicons and later the application of shotgun metagenomics, a more advanced and prompt method has been proposed for the detection of insidious pathogens in endophthalmitis. All pathogens, even those unculturable can be detected, without being limited by the starting primers [50][51] . Although NGS has the advantage of high throughput, its short-read characteristics render it difficult to identify repeats in gene sequences, followed by several other defects [52][53][54] .…”
Section: Molecular Diagnostic Techniques Of Endophthalmitismentioning
confidence: 99%
“…Afterwards, with the advent of an unbiased sequencing technique, the NGS of 16S rDNA amplicons and later the application of shotgun metagenomics, a more advanced and prompt method has been proposed for the detection of insidious pathogens in endophthalmitis. All pathogens, even those unculturable can be detected, without being limited by the starting primers [50][51] . Although NGS has the advantage of high throughput, its short-read characteristics render it difficult to identify repeats in gene sequences, followed by several other defects [52][53][54] .…”
Section: Molecular Diagnostic Techniques Of Endophthalmitismentioning
confidence: 99%
“…In previous studies, the causative bacterial species varied according to the endophthalmitis type. Notably, bacterial agents could not be identified in numerous cases, highlighting diagnostic challenges 22. Metagenomic analysis makes it possible to detect pathogenic bacteria at the species level 23 24.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, bacterial agents could not be identified in numerous cases, highlighting diagnostic challenges. 22 Metagenomic analysis makes it possible to detect pathogenic bacteria at the species level. 23 24 Previous reports have shown that a 16S rRNA metagenomic analysis encompasses the whole genomic DNA present in the sample, leading to potential issues with contamination.…”
Section: Discussionmentioning
confidence: 99%
“…Metagenomic analysis requires proper interpretation of the data collected, and many issues remain, including diagnostic thresholds and contamination. It was necessary to remove known background contaminants from the data of potential pathogens for each subject [30]. The big issues are the high cost and costly maintenance.…”
Section: Metagenomic High-throughput Next-generation Sequencing (Mngs)mentioning
confidence: 99%